2016
DOI: 10.1093/chemse/bjw113
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Cultural Adaptation of the Sniffin’ Sticks Olfactory Identification Test for US children

Abstract: Disorders associated with smell loss are common in adolescents. However, current odor identification tests focus on children from age 6 and older and no cross-cultural test has to date been validated and fully implemented. Here, we aimed to investigate how 3-to-11-year-old US children performed to an adapted and shortened (11 odors instead of 14) version of a European odor identification test-the Sniffin' Kids (Schriever VA, Mori E, Petters W, Boerner C, Smitka M, Hummel T. 2014. The "Sniffin'Kids" test: a 14-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…To avoid the bias of age-dependent odor learning, we included young children who were old enough to understand and perform an odor identification task. Recently, Cavazzana and colleagues reported that odor identification tasks in children younger than 5 years of age to be unreliable 48 , considering previous studies 39,46 . Although some studies have claimed that children as young as 3-4 years are able to perform an odor identification task [28][29][30] , results must be evaluated with caution.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid the bias of age-dependent odor learning, we included young children who were old enough to understand and perform an odor identification task. Recently, Cavazzana and colleagues reported that odor identification tasks in children younger than 5 years of age to be unreliable 48 , considering previous studies 39,46 . Although some studies have claimed that children as young as 3-4 years are able to perform an odor identification task [28][29][30] , results must be evaluated with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies examined even younger children starting at an age of 3 years 17, 23, 25, 26 . Some of them displayed difficulties like small sample size, incomplete measures 23 or unfamiliarity with the odors in the identification task 17, 26 while other results might be influenced through the instructions of parents 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Some of them displayed difficulties like small sample size, incomplete measures 23 or unfamiliarity with the odors in the identification task 17, 26 while other results might be influenced through the instructions of parents 25 . Most of them showed poor results for children under an age of 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive tests for olfactory performance such as the Sniffin' Sticks test battery, including all three components of threshold, discrimination, and identification testing, can take up to one hour, requiring additional personnel resources. For this reason, shorter screening protocols such as the Sniffin' Sticks identification test [33][34][35][36][37][38][39][40][41][42] were frequently administered in clinical practice. These screening tests became increasingly popular and extensively used worldwide, but were often less accurate and inconclusive 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…We chose the 16-item Sniffin' Sticks identification test to serve as the technical basis, since these 16 items are represented in the most widely used olfactory assessment tool in German-speaking countries and have been further adapted and validated for various other countries [33][34][35][36][37][38][39][40][41][42] . Regarding the procedure, we agreed on using the "Odor-Lines-On-Paper" method which has been validated for odor identification, discrimination, and threshold testing in previous studies of our working group 25,26 and has the potential for self-administration.…”
Section: Development Of Ssomixmentioning
confidence: 99%